2017
DOI: 10.1371/journal.pone.0178718
|View full text |Cite
|
Sign up to set email alerts
|

Preventability of early vs. late readmissions in an academic medical center

Abstract: BackgroundIt is unclear if the 30-day unplanned hospital readmission rate is a plausible accountability metric.ObjectiveCompare preventability of hospital readmissions, between an early period [0–7 days post-discharge] and a late period [8–30 days post-discharge]. Compare causes of readmission, and frequency of markers of clinical instability 24h prior to discharge between early and late readmissions.Design, setting, patients120 patient readmissions in an academic medical center between 1/1/2009-12/31/2010Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
4
15
0
Order By: Relevance
“…This is consistent with our prior work, which showed that factors related to the index hospitalization such as acute illness burden and discharge timing were more closely associated with early readmissions than late readmissions (13), and our follow-up work, which showed that mean preventability scores were significantly higher in this early period compared to the late period by blinded physician review in a single center study (31). In the current study, we were able to address our hypothesis directly with a geographically diverse multicenter sample, improving upon external validity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with our prior work, which showed that factors related to the index hospitalization such as acute illness burden and discharge timing were more closely associated with early readmissions than late readmissions (13), and our follow-up work, which showed that mean preventability scores were significantly higher in this early period compared to the late period by blinded physician review in a single center study (31). In the current study, we were able to address our hypothesis directly with a geographically diverse multicenter sample, improving upon external validity.…”
Section: Discussionsupporting
confidence: 92%
“…While the adjudicators were not explicitly instructed to make note of readmission timing as an aim of the original study, knowledge of readmission timing could have biased their assessment of preventability or informed their choice of location where an intervention to prevent the readmission would have been most effective. It should be noted that while the possibility of bias is present, the current study is consistent with our findings in our prior single center study where the methodology for physician adjudication did involve blinding the adjudicators to the timing of the readmission (31). Additionally, all of the sites included in our population were academic medical centers, where patients are often not local, and carrying out usual transitions in care processes can be a challenge.…”
Section: Discussionsupporting
confidence: 90%
“…Despite reproducibility of the model and the suggestion that early readmissions may have increased likelihood for preventability, to date, we are still unable to determine if this readmission tool can help to identify readmissions that are avoidable. Consideration of other factors, other than the time from discharge, may also coincide more definitively with avoidable readmissions that need to be done.…”
Section: Discussionmentioning
confidence: 99%
“…Other developed models may be generally more complex to utilize, such as the HOSPITAL score,16 which requires sodium levels upon discharge which may not be performed for every patient in routine clinical practice, and the LACE model, which had its utility tested in local populations17,18 and requires an additional computation of the Charlson Comorbidity Index 19. Despite reproducibility of the model and the suggestion that early readmissions may have increased likelihood for preventability,20 to date, we are still unable to determine if this readmission tool can help to identify readmissions that are avoidable. Consideration of other factors, other than the time from discharge, may also coincide more definitively with avoidable readmissions that need to be done.…”
mentioning
confidence: 99%
“…Despite intense focus on preventing 30-day readmissions, early readmissions within the first 7 days of hospital discharge may be more preventable than later readmissions (8-30 days post-discharge) [1][2][3][4][5][6]. Early readmissions are more closely related to potential gaps in care during the index hospitalization [4] or reflect premature discharge.…”
Section: Introductionmentioning
confidence: 99%